Prevalence of Deletional Alpha Thalassemia and Sickle Gene in a Tribal Dominated Malaria Endemic Area of Eastern India. (11th March 2014) - Purohit, Prasanta; Dehury, Snehadhini; Patel, Siris; Patel, Dilip Kumar
Abstract : Inherited hemoglobin disorders like alpha thalassemia and sickle gene are common in the Indian subcontinent. These disorders in the heterozygous state act as malaria resistance genes and influence the susceptibility to Plasmodium falciparum malaria. There is inadequate knowledge about the epidemiology of these malaria resistance genes in the tribal dominated malaria endemic region of the state of Odisha in eastern India. A cross sectional prevalence study was undertaken in 594 subjects in five tribal populations in this region, namely, Sahara (42.4%), Kutia Kandha (30.0%), Kuda (15.8%), Gond (9.8%), and Oraon (2.0%). Sickling test, Hb electrophoresis, HPLC, and molecular studies were undertaken to diagnose the prevalence of sickle allele, β -thalassemia allele, and deletional alpha thalassemia. Sickle and β thalassemia alleles were found in 13.1% and 3.4% of subjects, respectively. Sickle allele was found both in heterozygous (10.1%) and homozygous state (3.03%). The prevalence of alpha thalassemia was 50.84% with an allelic frequency of 0.37. Both α −3.7 and α −4.2 alpha thalassemia were detected with an allele frequency of 0.33 and 0.04, respectively. The high prevalence of alpha thalassemia and sickle gene in this population is probably due to selection pressure of endemic malaria in this part of India.